(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Here we propose that during the second half of the XIX Century, the debates between liberals and conservatives were marked by themes associated to education, immigration policy, the actions of the government toward social conflicts, and the relationship between the State and the Church; however, the social model that was imposed on the country after Independence was never questioned. The elite, beyond their political debates, was able in that way to circumvent the State, living by the income generated by the products that they exported, without paying taxes and without modernizing their agricultural and mining enterprises.